Phraseological Representation Of The Concept “Happiness” In Modern English (Texas Journal of Philology, Culture and History, 2025)
The concept of “happiness” is fundamental to human cognition and culture, yet its linguistic representation varies across languages and cultures. This article explores the phraseological expression of the concept “happiness” in Modern English, with a focus on its semantic features, metaphorical structure, cultural connotations, and cognitive framing. Drawing upon examples from idiomatic expressions, proverbs, and fixed phrases, the study reveals how happiness is encoded in English through diverse linguistic means that reflect emotional, social, and cultural dimensions.